Mahmoud Darwish : literature and the politics of Palestinian identity - Abu Eid, Muna, 1959- (WCI (London, England) ;, 2016)
"Mahmoud Darwish is the poet laureate of the Palestinian national struggle. His poems resonate across the entire Arab world and, more than any other single figure perhaps since the death of Yasser Arafat, he represents a unifying figurehead for Palestinian national aspirations. In this, the first comprehensive biography of Darwish in English, Muna Abu Eid examines the poet's intellectual status on two fronts - both national and public - and offers a critical assessment of Darwish's national and political life. Based on Darwish's own writings and interviews with people who worked with him and situating Darwish's poetry within the wider context of Palestinian struggles inside Israel, this book explores the influence of Darwish's life and work in the Palestinian territories and in the diaspora: from the destruction of his Galilee village and displacement of his family during the 1948 Nakba; to his return and 'infiltration' back into the homeland and the struggle for survival inside Israel; to his internal and external exiles in Haifa, Moscow, Cairo, Beirut, Tunisia, Paris and even Ramallah."--Bloomsbury Publishing